Guidelines for PM Internship Scheme: A Pilot Project (2024-25) - Dr. H M Naveen (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The Prime Minister’s Internship Scheme in Top Companies has been announced in the Budget 2024-25 (Scheme). It aims to provide internship opportunities to one crore youth in top 500 companies in five years. Through this Scheme, youth will gain exposure for 12 months to real-life business environment, across varied professions and employment opportunities. As per the guidelines, the word Internship, for the purpose of this Scheme is envisaged as an arrangement between the intern and the company in which the company provides an opportunity to the intern to get training gain experience and skills within the real-life environment of the business or organization that helps in bridging the gap between academic learning and industry requirements in turn, assisting enhancement of her/his employability. This Scheme is separate from all the existing schemes related to skill development apprenticeships, internship and student training programmes, etc. being implemented across all the State and UTs of India, will run independently of all such Central/State schemes. Under this scheme, the government of India will provide internships to all students who have completed their education. The Government of India will also provide financial assistance and a monthly stipend to all selected applicants under the scheme. The financial assistance under the scheme will be transferred directly to the selected applicant’s bank account.
Keywords: Guidelines; PM Internship Scheme; Pilot Project